Depok Eco-Friendly Library as an Educational Tourism Destination - Muhammad Ilham Nur Luthfianto; Diptya Anggita (International Journal of Glocal Tourism, 2022)
Purpose: This study is to design a library in Depok City in West Java, Indonesia, which is a Central Government which is adjacent to Jakarta (the nation’s Capital) as well as to be able to support the City of Depok as an education city, and infiltration area. Research methods: It uses a descriptive method and divides into three stages: (1) data exploration by collecting related data and existing site conditions, (2) site and building analysis, (3) building design and making 3d model’s design. Findings: Understanding of surrounding conditions will be very helpful in designing eco-friendly building. Like wise with the building and site design that adapts to local environmental conditions will also provide comfort for the users themselves and even the surrounding residents. Implications: Creating an environmentally friendly library design by implementing the library tourism attractiveness index system will certainly make people interested in visiting continuously and getting positive benefits. The local and wider community not only gain knowledge but also freshness and happiness.